STRATEGY FOR CREATIVE ECONOMY DEVELOPMENT IN THE CULINARY TOURISM SECTOR IN SAMPANG CITY USING THE SWOT METHOD - Umi Hakim Ukasyah, Ana; Anugrahini Irawati, S. (Universitas Islam Lamongan, 2024)
The culinary tourism sector in Sampang City was chosen because the creative economy driven by creative industries can develop human resources through knowledge, activities and innovation. Developing creativity is important to achieve progress and competitive advantage. However, in developing the creative economy in the culinary tourism sector, there are still various problems with human resources, product innovation, lack of service ideas, limited suppliers, unattractive packaging design, limited marketing and use of technology. This research aims to determine internal and external environmental factors in the creative economic development strategy in the culinary tourism sector of Sampang City. The research results show that the development strategy requires intervention from the relevant government so that problems can be resolved, such as holding training, always innovating products, improving packaging design to make it more attractive, increasing suppliers and investing in more modern technology. This research uses a qualitative descriptive method with informants from culinary business actors in Sampang City. This research uses SWOT analysis to anticipate threats by exploiting strengths, and overcome weaknesses by looking for opportunities, so that the development of the creative economy in the culinary tourism sector remains optimal.